Ariosto’s Astute Arrogance: The Construction of the Comic City in La Lena - O’Connell, Daragh (Renaissance and Reformation / Renaissance et Réforme, 2017)
This essay interrogates Ludovico Ariosto’s theatrical poetics by charting his developing sense of the theatrical space and his embrace of the contemporary. From an initial appropriation of Roman stage models to a more nuanced appreciation of the comic possibilities afforded through a modernizing use of the contemporary city as more than a mere backdrop, Ariosto inscribed his native Ferrara in comic form, at once a subversive antithesis to the idealized courtly city and a repository for comedic potentialities. This is most evident in two of his comedies: Il Negromante (1520; 1528) and, in particular, La Lena (1528), in which Ferrara (both named and unnamed) assumes an increasingly important role in the construction of the “comic city.” Ultimately, Ariosto’s transformation of theatrical tradition may be located in his interrogation and satirization of the vices and mores of Ferrara, resulting in the creation of one of the finest plays of the Italian Commedia erudita.